Problemas ligados ao álcool em centros de emergência (PLACE)—People experiencing homelessness with alcohol-related problems in Lisbon's emergency shelters during the COVID-19 pandemic: a description and analysis of a harm reduction intervention - Azevedo, Filipe Oliveira; Neto, Ana; Gama, Ana; Subtil, Ana; Fuertes, Ricardo; Pereira, Claúdia; Tavares, Joana; Medinas, Raquel Luis; Silva, Ana V.; Dias, Sónia (Frontiers in Psychology, 2023)
Introduction Alcohol-related problems disproportionally affect people experiencing homelessness. As the first wave of the COVID-2019 pandemic spread in 2020, a number of emergency shelters were opened in Lisbon. Increased difficulties in obtaining alcohol could have led to an increased incidence of alcohol withdrawal. Therefore, a low-threshold harm reduction intervention was introduced to these emergency shelters. This consisted of a fixed medication treatment, made available immediately for those with specific conditions, without the need for a medical evaluation or abstinence from alcohol, together with an offer of subsequent access to specialized addiction centers. The Problemas Ligados ao Álcool em Centros de Emergência (PLACE) study (alcohol-related problems in emergency shelters) is a retrospective mixed-methods observational study. It describes the demographic, health, and social characteristics of shelter users participating in the program and aims to evaluate the intervention as well as the experience of the patients, professionals, and decision-makers involved. Results A total of 69 people using shelters self-reported alcohol-related problems. Among them, 36.2% of the people accepted a pharmacological intervention, and 23.2% selected an addiction appointment. The take-up of the intervention was associated with better housing outcomes. A description of an individual's trajectory after leaving the shelter is provided. Discussion This study suggests that non-abstinence-focused interventions can be useful and well-tolerated in treating addiction in this population.